Development of Android-Based Learning Media - Febriyani Pioke; Fachrudin Zain Olilingo; Sri Endang Saleh; Heldy Vanni Alam; Abd. Rahman Pakaya; Meyko Panigoro; Radia Hafid (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop a learning media. This research was a type of development research by adapting the ADDIE development model (Analysis, Design, Development, Implementation). The object of this research was students in class IPA SMAN 1 Suwawa with a total of 117 students. The entire content of the material, media, and language in the learning media had to undergo an expert validation process to create draft II. Draft II then underwent product revisions in a limited trial and created draft III. Then, in a field trial with a total of 117 students, the response received a "very strong" percentage with a percentage of 94.50%, creating the final product improvement for researchers. The results of the research were creating learning media in the form of Android-based applications in employment subjects with details on the homepage feature, Basic Competency & Learning Objectives feature, learning material feature, Practice Questions feature, and About feature